Cyberstalker : hard lessons of internet safety - Rather, Dan; CBS News; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 2004)
Reports on potential dangers encountered online, with a special focus on the stalking of children through the internet
Host: Dan Rather ; CBS News correspondents: Peter Van Sant, Susan Spencer, Bill Lagattuta
DVD format
Keywords: Internet and children -- United States; Computer networks -- Social aspects